Rekam Jejak Kebudayaan Hindu di Indonesia (Perspektif Artefaktual) - I Kadek Edi Palguna (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Hinduism originated from the Indian region which came to Indonesia since early AD. This is the basis for this paper, in order to find out the traces of Hindu culture from the beginning of its arrival to its development until now. There are quite a lot of historical relics related to Hinduism culture. These relics are certainly evidence of Hindu civilization from the beginning of its arrival until now. On this occasion, we will briefly review the track record of Hindu culture in Indonesia based on archaeological or material remains. The data presented is library data collected from various sources, either in the form of books or journal writings. The data collected is in the form of qualitative data then analyzed and presented descriptively. The results of the discussion on the development of Hindu culture in Indonesia have actually developed since the beginning of AD, but in writing it is known that it began in the 4th century AD, based on the Yupa inscription data in Kutai. There are various forms of culture in the form of abandoned objects, namely inscriptions, statues and temples. These various forms of heritage have different styles and forms based on the styles that influenced them.Keywords: Hindu Culture, Artifactuals and Religions